The effect of spraying different disinfectants on condensational silicone impressions; an in vitro study - Hamid Badrian; Amin Davoudi; Meysam Molazem; Mohammad Hossein Zare (Wolters Kluwer Medknow Publications, 2015)
Background: Dentistry equipment are exposed to different types of pathogenic microorganisms. The aim of this study was to investigate the effect of spraying three different types of disinfectants on condensational silicones after 5 and 10 min. Materials and Methods: Totally, 66 circular samples of condensational silicone impression materials of 1 cm diameter and 2 mm thickness were contaminated by Staphylococcus aureus, Pseudomonas aeruginosa, and Candida albicans fungus. Except for control samples, all of them were disinfected with sodium hypochlorite (NaOCl) 0.525%, Deconex and Epimax by spraying method. Afterward, they kept in plastic bags with humid rolled cotton for 5 and 10 min. In order to isolate microbiotas, the samples were immersed in 2% trypsin for 1 h and diluted with normal saline in a portion of 1, 1/2, and 1/4. The trypsin suspensions were transferred to culture plates for incubation and colony-forming unit assay. The data were analyzed by Mann-Whitney test and SPSS software version 16 at a significant level of 0.05. Results: There was a meaningful difference between disinfection effects of Epimax-Deconex for all mentioned microorganisms after 5 min (P = 0.034), and between disinfection effects of NaOCl 0.525%-Epimax for S. aureus (P = 0.043) and P. aeruginosa (P = 0.046) after 5 min. Furthermore, there was a meaningful difference between disinfection effects of Epimax-Deconex (P = 0.034) and NaOCl 0.525%-Epimax (P = 0.034) for P. aeruginosa after 10 min. Conclusion: Condensational silicone can be effectively disinfected by spraying tested three disinfecting agents. More specifically, Deconex showed the best results compared to the other agents.